FOUR STARS OF LARGE PROPER MOTION IN THE ORION REGION - LUYTEN, WJ; HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1960)
We report on 4 stars with large proper motions in the Orion field.
BOL OBS TONAN TACUB
Keywords: FOUR STARS, LARGE PROPER, MOTION, ORION REGION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS